THE DILEMMA OF BPJS KESEHATAN (NATIONAL HEALTH INSURANCE) BILL FOR POOR PEOPLE IN RURAL COMMUNITY OF MERABUAN - Mulyono, Sri; Sihaloho, Nahot Tua Parlindungan; Sutarman,; Hutagaluh, Oskar; Sumar’in, (International Journal of Psychosocial Rehabilitation, 2020)
The public health insurance program launched by the government does not always benefit the community. It does not also harm the community, as done by the Agency for National Health Insurance (BPJS Kesehatan) program which is considered only beneficial for the upper economic class community. However, it is detrimental for the lower economic community as experienced by the majority of the people of Merabuan Village. The purpose of this study was to discuss the dilemma of the Social Security Organizing Agency (BPJS) contribution dilemma for the lower economic community in Merabuan VillageTo overcome the above problems, discussing in- depth interviews, observations and arranging were carried out successfully for some underprivileged residents in Merabuan Village. The results of this study indicate the health insurance program with the principle of mutual cooperation, at the time of approval did not go according to plan but the program had become a dilemma of bills that rose more than 100% which was very burdensome, especially for the lower economic community. Conclusion: On the one hand, the weak economy community asks for a health insurance program to lighten their economy, but approving the BPJS with a payment system based on a family member card considers it very burdensome for the economically weak Merabuan Village community.